2020
DOI: 10.1038/s41396-020-00756-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbial carrying capacity and carbon biomass of plastic marine debris

Abstract: Trillions of plastic debris fragments are floating at sea, presenting a substantial surface area for microbial colonization. Numerous cultivation-independent surveys have characterized plastic-associated microbial biofilms, however, quantitative studies addressing microbial carbon biomass are lacking. Our confocal laser scanning microscopy data show that early biofilm development on polyethylene, polypropylene, polystyrene, and glass substrates displayed variable cell size, abundance, and carbon biomass, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 59 publications
1
38
0
6
Order By: Relevance
“…The functions related to chemoheterotrophy, aerobic chemoheterotrophy, and fermentation were identified as the top three key differentiators of microplastic and water samples, confirming the enrichment of heterotrophs on microplastics. The potential reason can be that microplastics have the capacity to entrap organic carbon and nitrogen from the surrounding oligotrophic water (Zhao et al ., 2021). Overall, regarding both taxa composition and predicted functional groups, our results confirmed that microplastics may exert selection pressure on the formation of plastisphere communities.…”
Section: Resultsmentioning
confidence: 99%
“…The functions related to chemoheterotrophy, aerobic chemoheterotrophy, and fermentation were identified as the top three key differentiators of microplastic and water samples, confirming the enrichment of heterotrophs on microplastics. The potential reason can be that microplastics have the capacity to entrap organic carbon and nitrogen from the surrounding oligotrophic water (Zhao et al ., 2021). Overall, regarding both taxa composition and predicted functional groups, our results confirmed that microplastics may exert selection pressure on the formation of plastisphere communities.…”
Section: Resultsmentioning
confidence: 99%
“…For visualization of biofilms and plastic surfaces, several studies have applied scanning electron microscopy (SEM) ( Carson et al, 2013 ; Zettler et al, 2013 ; Bryant et al, 2016 ; Kirstein et al, 2018 , 2019 ; Miralles et al, 2018 ). With SEM analysis, Eukarya were identified, of which diatoms are early and/or dominant colonizers ( Eich et al, 2015 ; Dudek et al, 2020 ; Zhao et al, 2020 ). However, SEM does not allow the identification of the attached prokaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…Mined petrochemicals are the feedstock for making plastics. Consumer used and discarded plastic is blown by wind and moved by water flowing through landscapes into the world's ultimate trash receptacle, the world's ocean [1][2]; about 1% of microbial cells in the world-ocean surface microlayer inhabit plastic debris, making that debris an unnatural habitat for oceanic flora [3]. Freshwater runoff from streams and rivers which debauch into Rio de Janeiro's GB carry floating plastic debris which, upon natural comminution, becomes a major microplastic [4] contamination macro-problem within the Holocene gulf [5] as well as the adjacent continentalshelf [6].…”
Section: The "Plasticarianism"mentioning
confidence: 99%
“…The literature on pollution of the seas is vast and tends always to grow, particularly with regard to plastic waste [1,3,5,6,8,10]. The pollution caused by the accumulation of plastic in river estuaries, soils and oceans is perhaps the main signature of consumerism and slouch, traces of a radically aggressive and possibly lethal inhuman modern-day consumerist life-style.…”
Section: Introductionmentioning
confidence: 99%